ANALISIS IMPLEMENTASI DIGITALISASI SISTEM PERPAJAKAN DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DI INDONESIA - Faisal Sinaga; Muhammad Ali Guntur; Dini Vientiany (SYAHADAT: Journal of Islamic Studies, 2026)
The digitalization of the tax system is one of the Indonesian government's strategic efforts to improve administrative efficiency and taxpayer compliance. This study aims to analyze the implementation of tax system digitalization and its impact on taxpayer compliance in Indonesia. The research employs a qualitative approach using literature review techniques from various scientific journals and official reports related to digital taxation. The results indicate that digital systems such as e-Filing, e-Billing, and e-Invoicing (e-Faktur) enhance accessibility, transparency, and accuracy in tax reporting. This improvement has a positive effect on taxpayer compliance, both in terms of tax reporting and payment. However, the implementation of digital taxation still faces several challenges, including limited digital literacy, uneven internet access, and resistance from some taxpayers. Therefore, efforts to improve education, socialization, and digital infrastructure are necessary to optimize the effectiveness of the digital tax system.